Computerkriminalität im Europäischen Strafrecht Kompetenzverteilung, Harmonisierungen und Kooperationsperspektiven - Haase, Adrian (Internet und Gesellschaft, 2017)
Combatting computer crime requires transnational co-operation between law enforcement agencies as well as the harmonisation of criminal law. Adrian Haase assesses existing EU directives regarding cybercrime, and develops a network-specific definition to facilitate the demarcation of European and national competences.